1998
DOI: 10.1002/(sici)1098-2396(199811)30:3<275::aid-syn5>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Repeated treatment with the selective kappa opioid agonist U-69593 produces a marked depletion of dopamine D2 receptors

Abstract: U-69593, the selective K-opioid agonist, was repeatedly administered in single daily injections (0.32 mg/kg) to male, Sprague-Dawley rats. Two or ten days later, the rats were euthanized and dopamine D1 and D2 receptors were measured using (3H]SCH 23390 or [3H]sulpiride, respectively, in caudate putamen and nucleus accumbens. Two days after the last of three injections, dopamine D2 receptors in the caudate putamen were decreased by approximately 40%, with no change in D1 receptors. Dopamine D2 receptor number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 27 publications
1
26
1
Order By: Relevance
“…At first glance, there may seem a contradiction between the facilitating effects of kappa agonist treatment on sensitization to QNP observed in the present study and the reports in the literature showing that kappa agonists attenuate the response to QNP (Acri et al, 2001;Izenwasser et al, 1998), as well as sensitization to cocaine (Collins et al, 2001a, b;Shippenberg et al, 2001). However, there is a crucial difference in the timing of kappa agonist injections between our study and those reports: In the present study, the kappa agonist was always coadministered together with QNP.…”
Section: Dependence Of Kappa Effects On Dopamine Contextcontrasting
confidence: 99%
See 1 more Smart Citation
“…At first glance, there may seem a contradiction between the facilitating effects of kappa agonist treatment on sensitization to QNP observed in the present study and the reports in the literature showing that kappa agonists attenuate the response to QNP (Acri et al, 2001;Izenwasser et al, 1998), as well as sensitization to cocaine (Collins et al, 2001a, b;Shippenberg et al, 2001). However, there is a crucial difference in the timing of kappa agonist injections between our study and those reports: In the present study, the kappa agonist was always coadministered together with QNP.…”
Section: Dependence Of Kappa Effects On Dopamine Contextcontrasting
confidence: 99%
“…In particular, it had been proposed that the mu-and the kappa-opioid systems work in concert for the proper maintenance of dopamine release, and specifically that a tonically active mu-system in the ventral tegmental area promotes dopamine release, while a tonically active kappasystem in the nucleus accumbens suppresses dopamine release (Spanagel et al, 1992). Indeed, preexposure to morphine enhances the locomotor response to amphetamine (Vanderschuren et al, 1999;Vezina et al, 1989), while repeated doses of the kappa-agonist U69593 inhibit the locomotor response to subsequent challenges with cocaine (Collins et al, 2001a, b;Shippenberg et al, 2001) or QNP (Acri et al, 2001;Izenwasser et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Our finding that acute SalvA attenuatesFwhereas repeated SalvA administered in the activity chambers facilitatesFthe locomotor stimulant effects of a D1 receptor agonist supports this possibility. Previous work has shown that repeated treatment with the KOR agonist U-69593 in the home cage leads to decreased DA D2, but not D1, receptor levels in the dorsal striatum and a decrease in the locomotor stimulant effects of the D2 agonist quinpirole (Izenwasser et al, 1998). Although we did not observe an effect of acute or repeated SalvA on D2 receptor agonist-induced locomotor activity, our combined findings suggest that repeated activation of KORs alters DA receptor signaling in a context-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…The impairment of D2-mediated inhibition of DA release may result from a downregulation of DA D2 autoreceptors. Repeated administration of U-69593 decreased the number of DA D2 receptors in the caudate putamen by 40% but did not affect binding affinity (Izenwasser et al 1998). …”
Section: Discussionmentioning
confidence: 99%
“…The cocaine-induced increase in DA levels in the DSTR is augmented (Heidbreder et al 1998). These effects have been attributed to KOPr-mediated decreases in postsynaptic D2 receptor number and downregulation of presynaptic D2 receptors that regulate DA uptake and release (Acri et al 2001;Izenwasser et al 1998). Cocaine-antagonist-like effects of synthetic KOPr agonists are also observed following their acute administration.…”
Section: Introductionmentioning
confidence: 99%